2020
DOI: 10.1186/s13014-020-01550-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for esophagitis after hypofractionated palliative (chemo) radiotherapy for non-small cell lung cancer

Abstract: Introduction: Esophagitis influences quality of life and might cause treatment interruption and hospitalization. Previous studies of risk factors focused on curative treatment for non-small cell lung cancer (NSCLC), which often involves concomitant chemoradiation (CRT). Given the uncertainty around extrapolation of dose constraints, we analyzed risk factors in patients treated with hypofractionated palliative regimens. Patients and methods: A retrospective review of 106 patients treated with palliative radioth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Standard supportive measures such as analgesics and parenteral nutrition were initiated to manage esophageal toxicity. We have previously published esophageal dose constraints for palliative (chemo)radiotherapy, based on a smaller study [ 10 ]. As mentioned in that study, our current treatment planning strategy is to limit the maximum dose to the esophagus (Dmax), e.g., by accepting a planning target volume (PTV) coverage of <95% at the intersection with the esophagus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard supportive measures such as analgesics and parenteral nutrition were initiated to manage esophageal toxicity. We have previously published esophageal dose constraints for palliative (chemo)radiotherapy, based on a smaller study [ 10 ]. As mentioned in that study, our current treatment planning strategy is to limit the maximum dose to the esophagus (Dmax), e.g., by accepting a planning target volume (PTV) coverage of <95% at the intersection with the esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate radiation doses between 30 and 60 Gy, such as the Norwegian CONRAD regime (42 Gy in 15 fractions), are also endorsed in current guidelines, preferably in combination with platinum-based chemotherapy [ 8 , 9 ]. Both chemotherapy and radiation are highly likely to induce at least mild or moderate side effects [ 10 , 11 ]. Acute and sub-acute thoracic toxicities causing hospitalization or death are of particular concern in a palliative treatment setting, where the expected outcome is symptom improvement and/or prolongation of survival.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] found that the volume with the minimum dose of 60 Gy (V 60 ) of the esophagus was a key dosimetric factor to predict ARE. Several dose−volume histogram (DVH) dosimetric parameters of the maximum dose, average dose, the dose with a volume of 5 cc (D 5 cc ) and the volume received dose larger than 20 Gy, 30 Gy, 35 Gy, and 40 Gy (that are V 20, 30, 35, 40 ) of the esophagus [ 13 ] were recognized as predictors of ARE. Other studies also provided discrepant predictors from the esophagus DVH dosimetric parameters, such as V 50 , the equivalent doses, and D 2 cc [ 14 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…One explanation for these discrepancies involves the different DVH factors believed to be associated with ARE, for example, D 5 cc, 10 cc used by Nieder et al . [ 13 ], and equivalent doses (EUD) adopted by Butof et al . [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…3) Who is at increased risk of unplanned hospitalization? These questions were addressed in a single center retrospective study that utilized an updated, previously established database [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%